An analysis of advanced and specialist posts in diagnostic radiography: Do job descriptions describe advanced practice?. Issue 2 (May 2021) - Harris, M.A.; Snaith, B.; Adamson, H.K.; Foster, B.; Woznitza, N.
Abstract: Introduction: Underpinned by a multi professional advanced clinical practice (ACP) framework, role consistency in practice level and education has been advocated across allied health professions. However little research has evaluated ACP expectations in radiography. This study identified the capability requirements of advanced and specialist diagnostic radiographers and mapped these to home country advanced practice frameworks and the Society and College of Radiographers (SCoR) Education and Career Framework. Methods: A consecutive sample of UK job advertisements was collected over six months and analysed for role focus, professional and clinical responsibilities, reporting or procedural expectations and knowledge and experience. Qualitative content analysis was used to scrutinise capabilities during role mapping. Results: A total of 42 job descriptions were analysed across UK Trusts and Health Boards, with 31 roles (73.8%) containing the terms advanced or specialist. Half of the advertised roles expected proficiency in reporting (n = 21; 50%). Responsibilities mapped to the practice outcomes of the SCoR framework in 31 roles (n = 31/42; 73.8%). The English documents (n = 40/42; 95.2%) evaluated against the multi professional framework identified significantly (χ2 = 14.6; p < 0.01) fewer capabilities (n = 13/40; 32.5%). Clinical practice was reflected broadly in textual behavioural descriptors however, leadership, education and research responsibilities were internal and operational in nature. Conclusion: This analysis of diagnostic radiographer job descriptions has demonstrated that many posts advertised as 'advanced' differ from advanced practice roles defined by the multi professional ACP framework, although they meet professional body standards. Implications for practice: Utilisation of diagnostic radiographers as 'true' advanced clinical practitioners remains intermittent. Greater consistency in job descriptions is required to strengthen radiography advanced practice and support radiographer development.